Planning an effective communication strategy for tourism information centers (TICs) in managing product information - Ety Setiawati; Chondro Suryono (Surya Hijau Manfaat, 2026)
Linggarjati Village possesses significant historical and natural tourism potential, yet its information dissemination remains sporadic and decentralized. This study analyzes the necessity of a centralized Tourist Information Center (TIC) to bridge the information gap and promote local assets effectively. Using a descriptive analysis method with purposive sampling of 45 respondents, the research identifies a tourist profile dominated by young females (56.5%) and Gen Z (43.5%), who prioritize